Histology : a text and atlas : with correlated cell and molecular biology / Wojciech Pawlina, Michael H. Ross - Ross, Michael H.
Now in its seventh edition, Histology: A Text and Atlas is ideal for medical, dental, health professions, and undergraduate biology and cell biology students. This best-selling combination text and atlas includes a detailed textbook, which emphasizes clinical and functional correlates of histology fully supplemented by vividly informative illustrations and photomicrographs. Separate, superbly illustrated atlas sections follow almost every chapter and feature large-size, full-color digital photomicrographs with labels and accompanied descriptions that highlight structural and functional details of cells, tissues, and organs.